Peran Kader Surabaya Hebat dalam Mendorong Kesehatan Lansia di Kelurahan Gubeng Kota Surabaya - Vivi Oktaviani; Heryanto Susilo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2026)
This study was motivated by the low participation of older adults in health programs and the heavy digital administrative burden faced by the Kader Surabaya Hebat (KSH) in Gubeng Subdistrict. The central issue of this study is the role of KSH in promoting elderly health, along with the supporting and inhibiting factors. The objective of this study is to analyze the strategic role of KSH as agents of elderly health empowerment at the community level. The benefits of this research include theoretical contributions to the development of Non-Formal Education (NFE) and practical benefits for improving the quality of life for the elderly as well as optimizing government services. The theoretical framework of this study utilizes Role Theory, the concept of Andragogy, and Ecological Systems Theory. This research employs qualitative approach using a case study design. Research subjects were selected through purposive sampling involving community health workers, the elderly, health workers, and neighborhood association (RW) officials. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using the Miles, Huberman, and Saldana model, which includes data collection, data condensation, data presentation, and drawing conclusions. The results of the study indicate that KSHs perform a multidimensional role as health educators, facilitators of POSGA and R1N1 services, social motivators, and implementers of monitoring through the Sayang Warga (ASW) application. The effectiveness of these roles is driven by family support, intrinsic motivation, community solidarity through voluntary contributions (jimpitan), and interagency collaboration. However, there are obstacles in the form of digital administrative burdens (role overload), misalignment in coordination processes, and the declining physical condition of the elderly. The study concludes that strengthening the self-reliance of community health workers and simplifying the reporting system are crucial for sustainability.